PENGARUH AKUNTANTABILITAS DAN TRASNPARANSI PENGELOLAAN ANGGARAN TERHADAP KOMITMEN ORGANISASI - Nurul Arafah (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2021)
This study aims to determine the effect of Accountability and Transparency of the Budget Management Employee Organizational Commitment in SMAN 4 Sukabumi. Variabel used in this study is the Accountability and Transparency of the Budget Management Employee Organizational Commitment. The study population was all employees SMAN 4 Sukabumi, amounting to 98 people, with a total sample of 47 people. Results research shows that the accountability and transparency of budget management have a positive effect on organizational commitment of employees.